Validation Study of the Family Involvement Questionnaire–Elementary Version With Families in Belize. (June 2021) - Garbacz, S. Andrew; Hall, Garret J.; Young, Kaitlyn; Lee, Yen; Youngblom, Rachel K.; Houlihan, Daniel D.
The purpose of this study was to examine the factor structure of the Family Involvement Questionnaire–Elementary Version with families in Belize. Participants were 185 primary caregivers of children in primary education settings in Belize. Caregivers were given the Family Involvement Questionnaire–Elementary Version to measure their educational involvement in their children's schooling. Findings indicated the factor structure of the Family Involvement Questionnaire–Elementary Version in Belize was not congruent with the factor structures with samples from the United States and New Zealand. Exploratory factor analysis suggested a five-factor solution: (a) home-school communication, (b) home expectations and monitoring, (c) educational support, (d) school and community involvement, and (e) school attendance. In light of similar measurement studies in the literature, these data indicate that family educational involvement varies across geographic and cultural contexts. This suggests that interventions and policies to improve education outcomes via family involvement ought to consider the unique structure of families' involvement in the educational system.